Optimalisasi Budidaya Perikanan Melalui Digital Marketing di Panti Rehabilitasi Pondok Tetirah Dzikir - Lokita, Raden Arditya Mutwara; Bela Fataya Azmi; Sri Mulyatun; Rahma Widyawati; Rufki Ade Vinanda; Muh. Idris Purwanto (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Pondok Tetirah Dzikir Rehabilitation Center is a pesantren (Islamic boarding school) for people with mental disorders (ODGJ) and drug addicts, located in Berbah, Sleman. Established around 1999, the foundation of Pondok Tetirah Dzikir was driven by the concern of the caretakers for individuals with mental health issues. The main activity at the center involves regular dhikr (remembrance of God) five times a day after obligatory prayers, practiced by the residents who consist of ODGJ and drug addicts. The community recognizes the center as a free rehabilitation facility, even though it still requires funding to meet the daily needs of its approximately 170 residents. Providing basic necessities, such as three meals a day, presents a significant challenge due to financial constraints. The primary problem faced by the center is a lack of funding. To address this, a community service team from Universitas Amikom Yogyakarta conducted a training program titled "Optimization of Fish Farming in the Digital Marketing Era." The training was delivered through seminars and hands-on field practice on fish farming. The goal was to empower both the caretakers and residents to manage and optimize their existing fish ponds, thereby generating additional income for the center. The outcome of this community service activity indicated a strong understanding of both digital marketing concepts and practical fish farming, as demonstrated through direct implementation at the Pondok Tetirah Dzikir fish ponds.